INTEGRATED PLATFORM FOR TRANSFERRING KNOWLEDGE AND SKILLS IN AGRO-FOOD SECTOR IN ROMANIA - Stoian, Mirela; Ion Raluca, Andreea; Florin Dumitru, Frone (Economics of Agriculture, 2012)
This paper aims at presenting the integrated platform for transferring knowledge and skills in agro-food sector, as a tool for facilitating information exchange between stakeholders: businesses, centres of research, educational and research in the food and agro-business sector, centres of business incubation in the food sector, clusters of SMEs, technology transfer centres. The methodology consists of a web application, whose features are detailed. Main results of research show that the platform generates savings of time and financial resources through a simplified procedure and provides opportunities for documentation and collaboration correlated to the real needs of users.